Surface water pollution with nutrient components,trace metals and metalloidsin agricultural and mining-affected river catchments (A case study for three tributaries of the Maritsa River, Southern Bulgaria) - Radeva, Kalina; Seymenov, Kalina (Geographica Pannonica, 2021)
This work analyses changes in the content of nutrient components and trace metals and metalloids at three tributaries of the Maritsa River flowing in Southern Bulgaria with catchments affected by mining and agricultural activities. Input data includes information about 14 chemical water quality parameters (N-NH4, N-NO3, N-NO2, N-tot, P-tot, P-PO4, Al, As, Fe, Cu, Mn, Ni, Pb, and Zn) obtained from the Executive Environment Agency for the period 2015–2018. Two documented methods were used in this work to determine the pollution status of river waters – Heavy metal pollution index (HPI) and CCME Water Quality Index. The results based on the CCME WQI ranked water quality as “Poor” (WQI values range from 31.2to 39.9). The HPI ratings achieve scores exceeding the critical pollution value of 100 for some of the metals (Al, Cu, Mn, and Zn), which indicates that water is seriously polluted concerning those variables. Therefore, it can be summarized that the river waters are not appropriate for safe drinking, agriculture, and household use because of significant nutrient and metalloids and trace metals contamination.